Commensal Microbes and Hair Follicle Morphogenesis Coordinately Drive Treg Migration into Neonatal Skin - Scharschmidt, Tiffany C. (Cell Host Microbe, 2017)
Regulatory T cells (Tregs) are required to establish immune tolerance to commensal microbes. Tregs accumulate abruptly in the skin during a defined window of postnatal tissue development. However, the mechanisms mediating Treg migration to neonatal skin are unknown. Here we show that hair follicle (HF) development facilitates the accumulation of Tregs in neonatal skin and that upon skin entry these cells localize to HFs, a primary reservoir for skin commensals. Further, germ-free neonates had reduced skin Tregs indicating that commensal microbes augment Treg accumulation. We identified Ccl20 as a HF-derived, microbiota-dependent chemokine and found its receptor, Ccr6, to be preferentially expressed by Tregs in neonatal skin. The Ccl20-Ccr6 pathway mediated Treg migration in vitro and in vivo. Thus, HF morphogenesis, commensal microbe colonization, and local chemokine production work in concert to recruit Tregs into neonatal skin, thereby establishing this tissue Treg niche early in life.